(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The advent of IT has offered significant improvement to the way financial transactions in business are processed by professional accountants. Hence, in most parts of developed countries, it is almost impossible to function as an accountant without requisite IT skills. However, the pattern seem not attain similar forte in SMEs especially in developing economies. Consequently, this study would provide answer to the degree of computer-based accounting systems adoption by SMEs in India. E-Accounting is new development in field of accounting. E-Accounting might just be the beginning of a new era where world would be extending its arms to India with perspective that India is the place which can deliver the best”. So e-Accounting has visited India with a rainbow of opportunities. Online accounting through a web application is typically based on a simple monthly charge and zero-administration approach to help businesses concentrate on core activities and avoid the hidden costs associated with traditional accounting software such as installation, upgrades, exchanging data files, backup and disaster recovery.